Challenges in research data management practices: a literature analysis. (15th December 2022) - Birkbeck, Gail; Nagle, Tadhg; Sammon, David
ABSTRACT: Driven by funding and publishing requirements to open and reuse data, Research Data Management (RDM) has become a crucial part of a researcher's role. However, this key task is often completed by researchers, who sometimes make decisions, without having the necessary support or know-how, resulting in few research datasets being shared. The objective of this study is to identify the challenges in researcher RDM practices that impact the sharing/reusing of research data. Four thematic areas emerge from our coding of the selected literature: (i) alignment of research management and data management, (ii) resourcing, (iii) researcher openness, and (iv) research data governance. Despite the growing field of RDM, there is a limited understanding of RDM practiceshighlighting a requirement for further investigation together with practical tools, decision aids and training to assuage clearly unmet needs. Indeed, this provides an opportunity for the Information Systems (IS) community to better support researchers to implement good RDM practices.